OMNIA VINCIT AMOR: parody and tone in Ovid's Amores 3.11a&b - Shayne, Ryan (School of Languages and Literatures, 2026)
Ovid's Amores 3.11a&b has been discussed by many in passing, and few in detail. The poem contains the Ovidian lover's second attempt at a renuntiatio amoris, and (arguably) comprises two parts of a whole: in 3.11a, the lover boasts to have emancipated himself from love's shackles and proceeds to outline the reasons for his renunciation (largely his beloved's indiscretions); in 3.11b, however, he backtracks into a drawn-out internal conflict between his love and hate for her, that exhausts in elaborate detail the Catullan odi et amo idea. Because in this poem elegiac commonplaces abound, and because of Ovid's verbal dexterity and allusiveness, the poem has often been deemed simply a playful parody of or variation on the Catullan theme: that is, insincere and not at all serious. Few have considered the possibility that in 3.11 we ought to take Ovid more seriously than elsewhere. I aim to show that there is good reason to do so: that the poem's irony and humour need not preclude seriousness, and that its literariness does not come at the expense of emotional intensity. Ovid's elegiac lover in the Amores, like the praeceptor in the Remedia Amoris, treats love as a game to be won through strategy and artifice. I suggest that, in Am. 3.11, Ovid reflects on the inevitable failure of this approach. By considering Ovid's use of intertextuality and intratextuality, and the difference between the Ovidian lover's attitude in Am. 3.11 and elsewhere in the Amores, I argue that the poem voices a serious concern: the lover's attempts to conquer love inevitably fail, because love conquers all; it cannot be treated as a game, because it is not one — at least not one that he can win.